Performance Analysis of API Protocol Models as Recommendations for Developers in Application Development - Fhonna, Rizky Putra; Afrillia, Yesy; Ilhadi, Veri; Arif, Abdul Halim; Selian, Riko Ardiansyah (JINAV: Journal of Information and Visualization, 2024)
The evaluation of various API types reveals distinct strengths and weaknesses. REST APIs exhibit inefficient performance with high average response times and an error rate of approximately 14%, indicating potential delays and instability under load. SOAP APIs, with an average response time of 167 ms, perform better than REST in terms of speed but still lag behind GraphQL and have a slightly higher error rate of 14.80%. GraphQL demonstrates the fastest average response time at around 171 ms, offering high efficiency in data delivery, although its error rate is notably high at 15%, signaling a need for improved stability. RPC APIs, with an average response time of 238 ms, are less speedy compared to GraphQL and SOAP but excel in stability with a very low or zero error rate, making them highly reliable under high loads. Overall, GraphQL is optimal for applications requiring rapid data interaction, RPC is best suited for scenarios demanding high consistency and reliability, SOAP offers a middle ground, and REST may be appropriate for simpler, less demanding applications.